Promosi Kesehatan tentang Hypnobreastfeeding dalam Upaya Peningkatan Pengetahuan Ibu Postpartum - Nurbaiti Nurbaiti; Gustina Gustina (Jurnal Abdimas Kesehatan (JAK), 2022)
Mother's milk is a liquid that contains high nutrients which are very beneficial for optimal health, development and growth of babies. Breastfeeding is a scientific condition but there are still mothers who experience problems in breastfeeding such as work, workload, mothers feel stressed, tired, depressed and low self-confidence of the mother will affect the success of breastfeeding her baby where it can affect the physical and psychological condition of the mother. eventually will hinder the smooth in producing breast milk. The purpose of this service activity is carried out in the Work Area of the Kebon Kopi Health Center with the aim of this activity being to provide information and increase knowledge, as well as understanding post-partum and breastfeeding mothers and mothers can do it independently at home, this activity is carried out from March to March July 2021, assisted by 2 Midwifery students from STIKes Baiturrahim, the targets in this activity are post-partum mothers and breastfeeding mothers, the method used is lectures, question and answer and media discussions used are leaflets, then evaluated By giving questions to the mother, some of the questions she can answer well, the result of this activity is that the mother's knowledge increases and she can apply it independently. The results of this activity are published in health academic journals.